The Role of the NF-kB Pathway and Oxidative Stress Markers in the Protective Effects of Peperomia pellucida in a Gastroenteritis Model - Lisa Savitri; Fendy Prasetyawan; Yuneka Saristiana; Elfred Rinaldo Kasimo; Rochmad Krissanjaya; Cornelia Amanda; Konradus Klala Mebung (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Gastroenteritis is a common gastrointestinal disorder characterized by intestinal inflammation, epithelial damage, and oxidative stress. Activation of the nuclear factor kappa B (NF-kB) signaling pathway and excessive production of reactive oxygen species play key roles in its pathogenesis. Peperomia pellucida is a medicinal plant traditionally used for inflammatory and gastrointestinal conditions; however, its molecular mechanisms of action remain poorly understood. This study aimed to investigate the protective effects of P. pellucida extract in an experimental gastroenteritis model, with a particular focus on NF-kB pathway modulation and oxidative stress markers. Gastroenteritis was induced in experimental animals, followed by oral administration of P. pellucida extract at different doses. NF-kB p65 expression was assessed using molecular analysis, while oxidative stress was evaluated through malondialdehyde levels and antioxidant enzyme activities, including superoxide dismutase and catalase. Histopathological examination of intestinal tissue was also performed. The results demonstrated that P. pellucida treatment significantly suppressed NF-kB p65 activation, reduced lipid peroxidation, restored antioxidant enzyme activities, and improved intestinal histopathological features compared to the untreated gastroenteritis group. These findings indicate that P. pellucida confers intestinal protection by attenuating inflammation and oxidative stress, supporting its potential as a natural therapeutic agent for gastroenteritis.